2019
DOI: 10.1186/s41984-019-0035-x
|View full text |Cite
|
Sign up to set email alerts
|

Prognosis of acute subdural hematoma greater than 10 mm in thickness in head injury patients with an extension or no motor response to pain after resuscitation

Abstract: Background: Most of the studies that examined the prognosis of acute subdural hematoma (ASDH) in severe head injury patients stated their overall prognosis as one group. The aim of the present study was to assess the prognosis of ASDH of > 10 mm in thickness in head injury patients with an extension or no motor response to pain after resuscitation. Material and methods: This retrospective study reviewed the severe head injury patients admitted to our university hospitals from January 2014 to August 2017. The i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 12 publications
0
8
0
Order By: Relevance
“…Traffic accidents and fall accidents were the major mechanisms of trauma in patients with ASDH. 12 , 19 However, in our study assault by stick and stone, 41(35.7 %) was a major cause of trauma. Those patients who sustained road traffic accident had a higher number of unfavorable outcome compared to other mechanisms but was not statically significant (chi-square p = 0.187).…”
Section: Discussionmentioning
confidence: 47%
See 2 more Smart Citations
“…Traffic accidents and fall accidents were the major mechanisms of trauma in patients with ASDH. 12 , 19 However, in our study assault by stick and stone, 41(35.7 %) was a major cause of trauma. Those patients who sustained road traffic accident had a higher number of unfavorable outcome compared to other mechanisms but was not statically significant (chi-square p = 0.187).…”
Section: Discussionmentioning
confidence: 47%
“… 6 However, in other studies SAH was the most common finding. 7 , 19 In addition, hemorrhagic contusion was found significantly higher in unfavorable outcome group 31(52.5 %) (Chi-square p = 0.044).…”
Section: Discussionmentioning
confidence: 89%
See 1 more Smart Citation
“…In general, predictors of poor clinical outcome in elderly patients suffering from aSDH were extensively described [ 7 , 8 , 9 , 10 , 11 , 12 , 13 ]. Patients suffering from traumatic aSDH are known to have higher risk of developing SE associated with poor outcome [ 25 , 26 ].…”
Section: Discussionmentioning
confidence: 99%
“…In a prospective observational study reported by Weimer et al [ 6 ] on a mixed population of 116 patients with SDH, aside from old age, poor premorbid neurological status, admission Glasgow Coma Score (GCS), and history of smoking and fever during hospitalization were independent predictors for poor outcome. There are several series providing scores to predict the outcome in patients with SDH [ 7 , 8 , 9 , 10 , 11 , 12 , 13 ]. Apart from the abovementioned well-known outcome predictors, status epilepticus is an unrecognized prognostic factor in patients with surgical interventions for SDH [ 14 , 15 ].…”
Section: Introductionmentioning
confidence: 99%